Transmitting nautical and cosmographical knowledge in the 16th and 17th centuries: The case of Pedro Nunes1. (29th May 2019) - Almeida, Bruno
Abstract : While it is generally accepted that texts concerning navigation written by the Portuguese mathematician and cosmographer Pedro Nunes (1502–1578) were influential in erudite circles of Europe, less is known about the real impact and diffusion of his work among the less educated, such as professionals associated with sea voyages. Did Nunes' theoretical contributions reach the relevant artisans and practitioners? If so, how did this come about? This paper uses the case of Pedro Nunes to investigate how complex theoretical ideas were transmitted to artisans in early modern Europe. It begins by examining the ways in which Nunes managed to interface with practitioners while working as a cosmographer. Second, it focuses on how his ideas, techniques, and results were used and transmitted by other agents, such as fellow cosmographers, navigation teachers, or mathematical practitioners. This paper concentrates on the transmission of such knowledge through vernacular texts – mainly navigation manuals and class notes – produced in the Iberian Peninsula and England in the 16th and 17th centuries. It shows how these agents facilitated the convergence between two distinct intellectual worlds – those of scholars and those of artisans – by rendering highly mathematical subjects more accessible to practitioners.